The sinful state of man. A fragment from a systematic french-russian dictionary of religious lexis (part 2) - Nadezhda Zhukovskaia (Вестник Православного Свято-Тихоновского гуманитарного университета: Сериа III. Филология)
This work is a continuation of the publication of separate parts of the Systematic French-Russian Dictionary of Religious Vocabulary. This article is part of a larger section, Protagonistes de la religion chretienne, which includes the topics Dieu, Etres crees, Condition pecheresse de l'homme Attitudes et qualites requises des croyants, Fideles de Dieu (de l'Eglise). As with previous posts, the main goal is to present vocabulary relevant to the topic (without pretensions to theological interpretation). In some cases, we gave as a Russian equivalent not only the lexeme of the modern Russian language, but also Church Slavonicism (if it is found among the authors of the XX-XXI centuries), which has the mark church-arch. The general topic is quite extensive, so the publication is divided into two parts: the second part will begin with the fifth paragraph, and it will include lexemes and lexical expressions denoting specific manifestations of human sinfulness. As in previous publications, examples for individual items (phrases in quotation marks), as a rule, reveal the content of the concept and illustrate the use of the lexeme in the language. In most cases, they are composed of elements (both individual lexemes and phrases) appearing in French and Russian sources, but are not direct quotations. This work has been proofread by Ph.D. Comparative Theologian, vv. teacher of the Moscow Theological Academy, Archpriest Igor Vyzhanov, to whom I express my gratitude for the thoughtful reading and comments that I took into account.